Changes to oral anticoagulant therapy and risk of death over a 3-year follow-up of a contemporary cohort of European patients with atrial fibrillation final report of the EURObservational Research Programme on Atrial Fibrillation (EORP-AF) pilot general registry. (15th November 2018) - Boriani, Giuseppe; Proietti, Marco; Laroche, Cécile; Diemberger, Igor; Popescu, Mircea Ioachim; Riahi, Sam; Shantsila, Alena; Dan, Gheorghe-Andrei; Tavazzi, Luigi; Maggioni, Aldo P.; Lip, Gregory Y.H.; ,
Abstract: Background: Contemporary European data regarding patients with atrial fibrillation (AF) allow us to assess the use of oral anticoagulants (OACs) and long-term outcomes. Methods: Patients with AF presenting to cardiologists in 9 European Society of Cardiology participating countries were enrolled and followed-up for 3-years. Results: Among the 2119 patients (40.4% female; mean age 69 ± 11 years) the prevalent types of AF at baseline were first-detected (30.5%) and paroxysmal AF (27.0%). The composite of stroke/TIA/peripheral embolism/all-cause death at 3-years occurred in 18.2%, with first detected AF and permanent AF reporting the highest event rates (22.5% and 27.3%, respectively; p  < 0.0001). Age, diabetes mellitus, heart failure, restrictive cardiomyopathy, chronic kidney disease and no physical activity were significant predictors of all-cause death. Paroxysmal and persistent AF patients were more likely to be hospitalised than other types of AF (34.1% and 37.9%, p  < 0.0001). At follow-up, OAC drugs were used in 80.1% of patients, with non-vitamin K antagonists (NOACs) accounting for 24.3% of patients. OAC treatment at follow-up visits changed throughout time, with a shift from VKA to NOACs reported in 5.4% of the cases, while the reverse shift (from NOACs to VKA) occurred in 8.6%. Discontinuation of OAC was recorded in while in 9.5% of visits. Conclusions: Patients outcomes at 3-years follow-up differ according to type of AF at baseline, with worse outcomes in patients presenting with first-detected or permanent AF. Changes in the type of OAC use with shifts from NOACs to VKA and vice-versa are not uncommon, as were interruptions of OAC. Highlights: In a 3-years follow-up outcomes differ according to atrial fibrillation (AF) type. Patients with first-detected or permanent AF reported worse outcomes. Risk of all-cause death was independently associated with multiple comorbidities. Over 3-years 14% of patients shifted oral anticoagulant, while 9.5% discontinued.